Trade-offs for consolidating a green transformation: a case study of the land use sector in Costa Rica - Villalobos Jiménez, Alonso (2020)
This article analyzes emerging trade-offs for the consolidation of a green transformation in Costa Rica’s land use sector in a context of recent structural changes. In particular, the analysis focuses on the conditions that have driven national actions and policies, and their role in the land use transformation process for the agricultural, forestry and protected areas sub sectors, from 1986 to 2016. Based on analyses of the impacts of public policies on the rural landscapes in Costa Rica, we define three main trade-offs for the consolidation of a green transformation in Costa Rica: i) a decrease in the possibilities for forest owners to develop economic activities on their farms; ii) the high risk for rural populations to not being able to respond to climate change impacts, and iii) the high emissions and questioned working conditions of the current agro-export model to meet sustainable standards.